International Oil and Gas Conference and Exhibition in China 2010
DOI: 10.2118/130369-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Completions Roadmap to Shale-Play Development: A Review of Successful Approaches toward Shale-Play Stimulation in the Last Two Decades

Abstract: Almost three decades have passed since the early exploration of the north Texas, Barnett Shale. The Barnett serves as an example study for the shale lifecycle. Operators in North America have used the Barnett-shale development as a roadmap for the exploration of new shale plays like the Marcellus, Haynesville, and Eagleford. Each new shale play is unique in nature with respect to geologic setting, lithology, and production mechanism. It is useful to have a defined strategy for the discovery, development, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The following empirical exponential formulas Equations 5and 6are used to describe the variation of porosity and permeability with the pressure in fracture system to realize the actual pumping rate and time [36,53]: In Equations (5) and 6, φf is current fracture porosity; φf0 is original fracture porosity; Cfi is the fracture compressibility during injection, KPa −1 ; Pnet is net pressure within fractures (difference between original pressure and current pressure), KPa; kf is current fracture permeability, md; kf0 is original fracture permeability, md; mi is the permeability changing factor, KPa −1 (exponent empirically determined). Tiab et al [54] reported that the fracture compressibility was as much as two orders of magnitude higher than the matrix compressibility.…”
Section: Stress-dependent Porosity and Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The following empirical exponential formulas Equations 5and 6are used to describe the variation of porosity and permeability with the pressure in fracture system to realize the actual pumping rate and time [36,53]: In Equations (5) and 6, φf is current fracture porosity; φf0 is original fracture porosity; Cfi is the fracture compressibility during injection, KPa −1 ; Pnet is net pressure within fractures (difference between original pressure and current pressure), KPa; kf is current fracture permeability, md; kf0 is original fracture permeability, md; mi is the permeability changing factor, KPa −1 (exponent empirically determined). Tiab et al [54] reported that the fracture compressibility was as much as two orders of magnitude higher than the matrix compressibility.…”
Section: Stress-dependent Porosity and Permeabilitymentioning
confidence: 99%
“…In the process of stimulation, hydraulic fractures may connect and reactivate the already existing natural fractures or generate new induced fractures near the wellbore. Well productivity could be substantially increased if complex fracture networks are created by hydraulic fracturing [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is of great necessary to explore the relationship between rock mass properties and the hydraulic fracture geometry, so that we can predict what kind of fracture geometry tends to be generated in a specific reservoir. Recently, some rock properties such as brittleness [Chong et al, 2010] and geologic discontinuities [Warpinski and Teufel, 1987] have been studied, but the effect of the strength heterogeneity, a common but essential feature in rock, on the fracture geometry has not been fully investigated especially quantitatively. Thus, we attempt to bridge this gap with current simulation.…”
Section: Strength Heterogeneity Effect On Hydrofracturingmentioning
confidence: 99%
“…In the reservoir renovation process, slick‐water, which contains a small amount of modified polyacrylamide (drag reducing agent, DRA), is a preferred candidate for shale gas fracturing due to its cheap price and highest suitability . In particular, drag reduction (DR) performance is one of the basic features of slick‐water, so it is important to choose or synthesize a DRA with good DR performance in field applications.…”
Section: Introductionmentioning
confidence: 99%